Trends in liver cancer rehabilitation needs, disease burden, and attributable risk factors in China, 1990–2021 - Xiangping Han; Lei He; Shaoying Li; Yuxing Zhu (Scientific Reports)
Abstract This study investigates trends in liver cancer rehabilitation needs, disease burden, and attributable risk factors in China from 1990 to 2021 using data from the Global Burden of Disease Study 2021. Key metrics included age-standardized prevalence (ASPR), years lived with disability (YLDs), and risk factor attribution. Between 1990 and 2021, the number of liver cancer patients requiring rehabilitation surged by 100.1% (132,779 to 265,539 cases), with YLDs rising by 102.8% (22,981 to 46,602). While ASPR and age-standardized YLD rates (ASYR) showed modest declines (ASPR: − 0.1% annual change; ASYR: − 0.23%), males exhibited a disproportionately higher burden, with 2021 cases and YLDs 2.98- and 2.74-fold greater than females, respectively. Risk factor analysis revealed smoking (14.0%), drug use (11.5%), and alcohol consumption (11.4%) as primary contributors, while metabolic factors like high BMI (7.5%) and fasting plasma glucose (1.9%) demonstrated accelerating impacts (YLDs EAPC: + 4.47% and + 1.31%, respectively). Aging populations and shifting etiologies drove increased rehabilitation demands, particularly among those ≥ 80 years. These findings underscore urgent needs for gender-specific interventions targeting modifiable risks and integrated nursing rehabilitation strategies to mitigate China’s growing liver cancer burden.